Notes from the Center of Turtle Island - Champagne, Duane (Rowman & Littlefield Publishers, 2010)
Duane Champagne has been presenting a series of comments on Indian policy, history, and culture since October 2006 in the newspaper Indian Country Today. This book provides a compilation of many of these editorials, plus two chapters not previously published. The contemplative writing by this well-respected scholar are comments and thoughts on a variety of issues that have arisen in his academic work and the classroom, but mainly through his direct contact and work with tribal communities. The purpose of these thought-provoking editorials is to create discussion about the issues that confront indigenous peoples and to educate a broad audience about the complexities of American Indian issues. Students, policy makers, and all people interested in American Indian or indigenous people's issues will find this book to be an interesting and stimulating read.